The Effects of Different Nanoadditives on the Physical and Mechanical Properties of Similar Silty Mudstone Materials - Ji-jing Wang; Zhen-ning Shi; Ling Zeng; Shuang-xing Qi (Advances in Civil Engineering)
In order to analyze the influence of different nanoadditives on the physical and mechanical properties of similar silty mudstone materials, nano-TiO2 (NTi), nano Al2O3 (NAl), and nanobentonite (NBe) were added to improve the physical and mechanical properties of silty mudstone similar materials. The physical and mechanical parameters are more in line with silty rock. Finally, nanometer additives suitable for silty mudstone similar materials are determined by conducting density test, natural water absorption test, uniaxial compression test, splitting test, softening coefficient test, expansibility test, and microscopic test. The effects of adding NTi, NAl, and NBe on improving the physical and mechanical properties of silty mudstone similar materials were studied to analyze the influence law of different NTi, NAl, and NBe contents on similar material density, natural water absorption, uniaxial compressive strength, tensile strength, softening coefficient, expansion rate, and other physical and mechanical parameters. The microscopic morphology of similar materials was analyzed by scanning electron microscopy and the mechanism of influence of nanoadditives on the microscopic structure of samples was revealed. The results are as follows. (1) The density of similar materials of silty mudstone increases with the increase of the content of nanoadditive. The natural water absorption rate decreased first and then increased with the increase of the content of nanometer additives, while the softening coefficient decreased with the increase of the content of nanometer additives. The uniaxial compressive strength and tensile strength increased first and then decreased with the increase of the content of nanometer additives. This is due to the incorporation of the nanoadditive amount effective to promote the hydration reaction of gypsum and accelerate the production of cement, while a similar material may be filled in the pores, reducing the internal defects, a similar material to make denser; when excessive dosage, nanoadditives agglomeration occurs, resulting in deterioration of the effect, but will reduce the mechanical properties of similar materials. (2) When the content of NBe is 6%, the physical and mechanical parameters of similar materials can reach or be closer to the silty raw rock except uniaxial compressive strength. The failure mode of the uniaxial compression specimen is also the same as that of the original rock, which can be used as the best choice. The research results laid the foundation for further analysis of NBe application in similar materials.